1997
DOI: 10.1074/jbc.272.19.12601
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Amyloid β-Peptide Fibril Formation with Protease-stable Ligands

Abstract: We have previously shown that short peptides incorporating the sequence KLVFF can bind to the ϳ40-amino acid residue Alzheimer amyloid ␤-peptide (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
219
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(228 citation statements)
references
References 32 publications
8
219
0
1
Order By: Relevance
“…It is tempting to speculate that RO-47-1816/001, after it has bound to the amyloid fibril, binds to the soluble peptide and brings it into close proximity to the fibril (Fig. 8), thereby facilitating docking of the peptides via their specific binding sequences (20,21,36). Whether cross-linking is mediated directly by RO-47-1816/001 or by a composite surface of RO-47-1816/001 and the A␤ polymer is not clear.…”
Section: A␤ Ligands Structurally Related To Ro-47-1816/001mentioning
confidence: 99%
“…It is tempting to speculate that RO-47-1816/001, after it has bound to the amyloid fibril, binds to the soluble peptide and brings it into close proximity to the fibril (Fig. 8), thereby facilitating docking of the peptides via their specific binding sequences (20,21,36). Whether cross-linking is mediated directly by RO-47-1816/001 or by a composite surface of RO-47-1816/001 and the A␤ polymer is not clear.…”
Section: A␤ Ligands Structurally Related To Ro-47-1816/001mentioning
confidence: 99%
“…Tjernberg and coworkers demonstrated a specific interaction of an immobilized peptide with full-length A (30). Other studies have focused on observing the growth of immobilized amyloid fibrils (31).…”
mentioning
confidence: 99%
“…These amyloidogenic sequences (for example, NAC region in a-syn, SNNFGAILSS in IAPP, FNNGNCFIL in gelsolin, [27] the AGAAAAGA repeat in the prion protein (PrP) [28] ) which have been shown to be crucial in initiating and/or driving the fibrillization of these proteins. Although several studies have reported small peptide-based inhibitors that are designed to target these regions within full-length Ab, [29,30,31] IAPP [32,33] and a-syn, [34] the hydrophobicity and reduced solubility of these sequences have precluded efforts to use them in high-throughput screening aggregation assays.…”
Section: Discussionmentioning
confidence: 99%